Native American ancestry and breast cancer risk in Colombian and Mexican women: ruling out potential confounding through ancestry-informative markers - Zollner, Linda; Torres, Diana; Briceno, Ignacio; Gilbert, Michael; Torres-Mejía, Gabriela; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Hamann, Ute; Lorenzo Bermejo, Justo (Breast cancer research, 2023)
Background  Latin American and Hispanic women are less likely to develop breast cancer (BC) than women of Euro‑pean descent. Observational studies have found an inverse relationship between the individual proportion of Native American ancestry and BC risk. Here, we use ancestry-informative markers to rule out potential confounding of this relationship, estimating the confounder-free effect of Native American ancestry on BC risk. - Methods and study population  We used the informativeness for assignment measure to select robust instrumental variables for the individual proportion of Native American ancestry. We then conducted separate Mendelian rand‑omization (MR) analyses based on 1401 Colombian women, most of them from the central Andean regions of Cundi‑namarca and Huila, and 1366 Mexican women from Mexico City, Monterrey and Veracruz, supplemented by sensitivity and stratified analyses. - Results  The proportion of Colombian Native American ancestry showed a putatively causal protective effect on BC risk (inverse variance-weighted odds ratio [OR] = 0.974 per 1% increase in ancestry proportion, 95% confidence interval [CI] 0.970-0.978, p = 3.1 × 1 0-40). The corresponding OR for Mexican Native American ancestry was 0.988 (95% CI 0.987-0.990, p = 1.4 × 1 0-44). Stratified analyses revealed a stronger association between Native American ancestry and familial BC (Colombian women: OR = 0.958, 95% CI 0.952-0.964; Mexican women: OR = 0.973, 95% CI 0.969-0.978), and stronger protective effects on oestrogen receptor (ER)-positive BC than on ER-negative and triple-negative BC. - Conclusions  The present results point to an unconfounded protective effect of Native American ancestry on BC risk in both Colombian and Mexican women which appears to be stronger for familial and ER-positive BC. These find‑ings provide a rationale for personalised prevention programmes that take genetic ancestry into account, as well as for future admixture mapping studies.
Gesehen am 19.12.2023